Non-conviction-based (NCB) asset forfeiture concept from a legal and human rights perspective - Pongkor, Dionysius Yasmin (The International Journal of Politics and Sociology Research, 2025)
This study examines the concept of Non-Conviction-Based (NCB) asset forfeiture through a human rights perspective, focusing on the balance between effective law enforcement and the protection of individual rights. NCB forfeiture enables the state to confiscate assets linked to criminal activity without requiring a prior conviction, making it particularly relevant for addressing corruption, money laundering, and organized crime. However, this mechanism raises concerns regarding property rights, due process, and potential state overreach. The analysis applies three theoretical frameworks, rule of law, due process theory, and property rights theory, to evaluate the legitimacy of NCB practices. Indonesia’s legal and human rights framework, including the 1945 Constitution, Law No. 8/2010 on Money Laundering, Law No. 31/1999 jo. Law No. 20/2001 on Corruption, Law No. 39/1999 on Human Rights, and Law No. 12/2005 ratifying the ICCPR, demonstrates the requirement for fairness and judicial oversight in asset forfeiture procedures. Findings indicate that NCB forfeiture can be compatible with human rights standards if implemented with strict safeguards, transparent procedures, and clear evidentiary thresholds. The study concludes that a comprehensive Asset Forfeiture Law is necessary to reinforce accountability, protect individual rights, and strengthen Indonesia’s asset recovery regime.